Experimental Work to Study the Behavior of Proppant Inside the Hydraulic Fractures and the Plugging Time - Abdul Ameer, Mohammed; Hamed Allah, Samera (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Experiments were conducted to study the behavior of the solid particles (proppant) inside the hydraulic fracture during the formation stimulation, and study the effect of the proppant concentration on the hydraulic fracturing process, which lead to bridge and screen-out conditions inside the fractures across the fracture width that restricts fracturing fluid to flow into the hydraulic fracture. The research also studies the effect of the ratio between the fracture size and the average particles diameter “proppant", on fracture bridging. In this study two ratios were considered β= 2 and 3 ,where β=Dt / Dp where: Dt= hydraulic fracture size (width) and Dp=Average particles diameter.This work presents experimental work to study the behavior of these particles (proppant) inside the hydraulic fractures by measuring the plugging time for different particles concentration for different conditions. The experimental data recorded for different particle concentration and one flowing forces (gravity) inside the hydraulic fracture. Most recorded experimental data obtained were analyzed by using SPSS software.